Dynamic Software Product Lines. - Hallsteinsen, Svein; Hinchey, Mike; Sooyong Park; Schmid, Klaus (Computer (00189162), 2008)
This article discusses dynamic software product lines (DSPL). Because it is impossible to foresee all the functionality or variability a software product line (SPL) requires, there is a need for dynamic SPL that produce software capable of adapting to fluctuations in user needs and evolving resource constraints. DSPL binds variation points at runtime, initially when software is launched to adapt to the current environment, as well as during operation to adapt to changes in the environment. The properties of DSPL and the growing interest in DSPL are described.